Validation of KASP Markers Associated with Hydrogen Cyanide in Fresh Cassava Roots in Uganda Cassava Germplasm - Kanaabi, Michael;; Mukasa, Settumba B.;; Nuwamanya, Ephraim ;; Iragaba, Paula;; Baguma, Julius Karubanga;; Nanyonjo, Ann Ritah;; Wagaba, Henry;; Muhumuza, Nicholas;; Namakula, Fatumah Babirye;; Wembabazi, Enoch;; Ozimati, Alfred;; Kayondo, Ismail Siraj;; et al. (MDPI AG, 2024)
Low hydrogen cyanide (HCN) concentration is a high-priority trait for cassava varieties targeting their fresh and dry product profiles. To be acceptable, varieties bred and developed for these market segments must meet international safety standards for maximum acceptable residual levels of cyanide in cassava food and food products. The discovery of molecular markers that co-segregate with low HCN has not yet resulted in widespread usage in marker-assisted selection (MAS) in breeding programs. To deploy these HCN markers in regular MAS, assessing their reliability in various genetic backgrounds is crucial. The aim of this study was to assess the predictive accuracy of trait specific markers for HCN. The study used six HCN kompetitive allele-specific polymerase chain reaction (KASP) markers that had previously been developed in a Brazilian population and verified in segregating West African cassava populations. For most markers used in the study, the average call rate was more than 91.7%. Three markers—snpME00404, snpME00405 and snpME00406—showed a significant co-segregation of genotypes with the HCN phenotype. On average, genotypes that carried at least one copy of the favourable allele had lower HCN scores. The proportion of phenotypic variance accounted for by the three most important markers was 14% (snpME00406), 17% (snpME00405) and 27% (snpME00404). The validation of identified HCN SNP-markers marks a significant step in their deployment to support selection and advancement decisions in cassava breeding programs. Agricultural Science Database